Effects of Nitrogen Application Rate and Transplanting Density on Dry Matter Production and Nitrogen Use Efficiency of Double Cropping Hybrid Rice - Ailong SHI; Haijun ZHU; Can WEN; Tian WEN; Xuehua WANG (Guangdong nongye kexue, 2022)
【Objective】The study was carried out to study the effects of nitrogen application rate and transplanting density on dry matter production and nitrogen use efficiency of double cropping hybrid rice.【Method】Zhuliangyou 819 was used as early rice material and Taiyou 398 was used as late rice material. Three nitrogen application levels (N1, N2, N3 at 0, 120, 150 kg/hm2 for early rice and N1, N2, N3 at 0, 150 and 225 kg/hm2 for late rice, respectively) and three transplanting densities(M1, M2, M3 at 13.3 cm×16.7 cm, 13.3 cm×20.0 cm, 16.7 cm×20.0 cm for early rice and M1, M2, M3 at 16.7 cm×20 cm, 16.7 cm×23.3 cm, 16.7cm×26.7cm for late rice, respectively).【Result】Increasing nitrogen fertilizer can significantly improve the accumulation of dry matter quality of rice, and the effect of transplanting density on dry matter quality is small. The dry matter quality of early and late rice is the highest in N3M1 treatment at maturity, in which the dry matter quality of early rice is 8.81%- 110.24% higher than that of other treatments, and that of late rice is 9.12%-117.12% higher than that of other treatments. The nitrogen uptake and utilization efficiency of early rice N2M2 treatment was up to 60.73%, and that of late rice N2M3 treatment was up to 63.20%. Increasing nitrogen fertilizer could not significantly improve the contribution rate to yield, and had little effect on the harvest index of late rice; Increasing nitrogen fertilizer application in early and late rice could significantly increase the total nitrogen accumulation of rice, with an increase of 67.50%-77.03% in early rice and 73.18%-115.12% in late rice; Each fertilization treatment of early rice had little effect on the agronomic and physiological utilization efficiency of nitrogen fertilizer. The increase of agronomic and physiological utilization efficiency of nitrogen reduction treatment of late rice was 52.66% and 59.00%; Nitrogen reduction in early and late rice can improve the partial fertilizer productivity of rice, and the growth rates of early and late rice are 15.54% and 48.58% respectively. The contribution rates of transplanting density to the yield of early and late rice were 18.52%-47.22% and 23.42%-35.42% higher in M3 treatment than in M1 and M2 treatment, respectively; It had little effect on total nitrogen accumulation, harvest index, agronomic utilization rate and partial fertilizer productivity; Low planting density can improve the physiological utilization rate of early rice, with an increase of 52.19%-144.14%, but it has little effect on the physiological utilization rate of late rice.【Conclusion】Therefore, N2M2 and N3M3 treatment can maintain high nitrogen use efficiency and dry matter accumulation of double cropping hybrid rice, and N2M2 treatment can save fertilizer and maintain high nitrogen use ability.